Helena, de Tróia ao cinema latino-americano: Cinzas do paraíso, de Marcelo Piñeyro (Argos, 2025)
Representations of Helen of Troy, as an individualized mythic character or as a metaphor for female condition, are widespread in western literature and iconography. In this paper I will analyse the Latin American film Cenizas del paraíso, by Marcelo Piñeyro. I will try to show how it can be seen as a very particular rereading of the myth of Helen in the contemporary Argentina.
Keywords: Helen of Troy; myth; Cenizas del paraíso